The Influence of Whistleblowing, Forensic Accounting, Professional Skepticism, and Investigative Audits on Fraud Detection (A Study on Representatives of BPK and BPKP) - Putri Mai Sarah; Taufeni Taufik; Suci Nurulita (Universitas Muhammadiyah Makassar, 2025)
This study examines the impact of whistleblowing, forensic accounting, professional skepticism, and investigative audits on fraud detection in the public sector, with a specific focus on auditors at the BPK and BPKP Representative Offices in Riau Province, Indonesia. The research adopts a quantitative design, using primary data collected through questionnaires distributed to all 95 auditors, applying a saturated sampling technique. Data analysis was conducted using multiple linear regression with IBM SPSS version 30. The findings demonstrate that whistleblowing, forensic accounting, professional skepticism, and investigative audits each have a significant and positive effect on fraud detection. Among these, professional skepticism and forensic accounting practices were identified as particularly influential factors in enhancing the ability of auditors to uncover fraud. The theoretical contribution of this study lies in expanding the literature on fraud detection in the context of emerging economies, emphasizing the role of whistleblowing mechanisms, forensic accounting tools, and auditors’ professional judgment. From a practical perspective, the results underscore the importance of improving auditors’ competencies through continuous training, strengthening investigative audit procedures, and promoting organizational cultures that encourage whistleblowing. These findings provide valuable insights for policymakers, auditing institutions, and scholars interested in improving the effectiveness of fraud detection within government auditing bodies. Ultimately, the study highlights the need for integrated strategies that combine technical, ethical, and organizational elements to enhance audit quality and accountability in the public sector.